Sprememba namembnosti londonskih kristalnih palač - Slivnik, Lara (Urbani izziv, 2003)
The architecture and use of both London crystal palaces, namely Crystal Palaceat Sydenham and Alexandra Palace on Muswell Hill are described. They share some common characteristics. Built for two World Fairs, their iron structure was later disassembled, remodelled and consequently rebuilt slightly modified at another location. Both were located outside the city centre, at a central viewpoint within a vast park. Both hosted cultural, educational, and sports events and in the second half of the nineteenth century became the two most visited London leisure time attractions. Advantages and drawbacks of the crystal palace as a building type are reviewedand the role of crystal palaces in Ebenezer Howard's Garden City is stressed.
Keywords: gradbene konstrukcije; gradbeni materiali; javne zgradbe; les; namembnost; železo